PROGRAM BK UNTUK MENINGKATKAN KETERAMPILAN KOMUNIKASI ANTARPRIBADI PESERTA DIDIK SMP NEGERI KABUPATEN BEKASI - Aliva Muyassar; Herdi Herdi (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
The guidance and counseling program is an effort to help individuals improve their communication skills, learn about good ways of communicating, and respect the other person. This study aims to describe the implementation of the guidance and counseling program in improving the communication skills of class VII students of SMP. this really needs to be researched because guidance and counseling services in junior high schools help students to practice interpersonal communication skills. Descriptive technique with a quantitative approach, thus obtained 69.4% in the category of medium communication skills, and as much as 30.6% in the category of low communication skills. According to data collected from 36 respondents, the students' communication skills were sufficient as expected for grade VII junior high school level.